Leprosy in premodern medicine : a malady of the whole body - Demaitre, Luke E., 1935- (Johns Hopkins University Press, 2007)
While premodern poets and preachers viewed leprosy as a "disease of the soul," physicians in the period understood it to be a "cancer of the whole body." In this innovative study, medical historian Luke Demaitre explores medical and social perspectives on leprosy at a time when judicious diagnosis could spare healthy people from social ostracization and help the afflicted get a license to beg.